Convenient approach to polyoxygenated dibenzo[c, e]pyrrolo[1, 2-a]azepines from donor–acceptor cyclopropanes. Issue 19 (31st August 2018) - Boichenko, Maksim A.; Ivanova, Olga A.; Andreev, Ivan A.; Chagarovskiy, Alexey O.; Levina, Irina I.; Rybakov, Victor B.; Skvortsov, Dmitriy A.; Trushkov, Igor V.
Abstract : A convenient approach to polyoxygenated tetrahydrodibenzo[ c, e ]pyrrolo[1, 2- a ]azepines from the donor–acceptor cyclopropanes has been developed. Abstract : A short convenient approach to polyoxygenated tetrahydrodibenzo[ c, e ]pyrrolo[1, 2- a ]azepines from the donor–acceptor cyclopropanes was developed. A simple synthetic sequence involves: (a) cyclopropane ring opening with azide ion and Krapcho dealkoxycarbonylation; (b) azide-to-imine transformation followed by imine reduction; (c) the oxidative cyclization of 5-aryl-1-benzylpyrrolidin-2-ones, the key intermediates for this approach.